Paying for what kind of Performance? Performance Pay and Multitasking in Mission-Oriented Jobs - Daniel Jones; Mirco Tonin; Michael Vlassopoulos (Center for Economic Studies and ifo Institute (CESifo), 2018)
How does pay-for-performance (P4P) impact productivity, multitasking, and the composition of workers in mission-oriented jobs? These are central issues in sectors like education or healthcare. We conduct a laboratory experiment, manipulating compensation and mission, to answer these questions. We find that P4P has positive effects on productivity on the incentivized dimension of effort and negative effects on the non-incentivized dimension for workers in non-mission-oriented treatments. In mission-oriented treatments, P4P generates minimal change on either dimension. Participants in the non-mission sector – but not in the mission-oriented treatments – sort on ability, with lower ability workers opting out of the P4P scheme.
Keywords: C91; M52; J45; 330; prosocial motivation; performance pay; multitasking; sorting